2018
DOI: 10.1016/j.ejca.2018.09.025
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of nivolumab in combination with ipilimumab in Japanese patients with advanced melanoma: An open-label, single-arm, multicentre phase II study

Abstract: The aim of the study was to evaluate the efficacy and safety of nivolumab combined with ipilimumab in treatment-naïve Japanese patients with advanced melanoma. Methods: In this multicentre, single-arm study, treatment-naïve Japanese patients with unresectable stage III/IV or recurrent melanoma received nivolumab (1 mg/kg) plus ipilimumab * Results of this study were partly presented at the European Society for Medical Oncology Asia Congress 2017, 17e19 November, Singapore.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
63
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 53 publications
(74 citation statements)
references
References 32 publications
(36 reference statements)
6
63
5
Order By: Relevance
“…Another study (Reck et al, 2019) showed that first-line NIVO + IPI led to continuous early improvement in patients with advanced NSCLC and high TMB compared with chemotherapy. Japan's single-arm experiment (Namikawa et al, 2018) also highlighted the advantages of NIVO + IPI.…”
Section: Discussionmentioning
confidence: 99%
“…Another study (Reck et al, 2019) showed that first-line NIVO + IPI led to continuous early improvement in patients with advanced NSCLC and high TMB compared with chemotherapy. Japan's single-arm experiment (Namikawa et al, 2018) also highlighted the advantages of NIVO + IPI.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 37 evaluable patients, the confirmed overall response rate was 24% in those with cutaneous melanoma and 25% in those with mucosal melanoma. A phase II trial of nivolumab and ipilimumab combination therapy was recently completed [ 50 •]. A total of 30 patients, including seven with acral and 12 with mucosal melanoma, were enrolled.…”
Section: Introductionmentioning
confidence: 99%
“…To date, only a Japanese phase II clinical study has demonstrated the efficacy and safety of this treatment in Japanese patients. However, only 30 treatment‐naive patients were included 17 . Thus, the efficacy of nivolumab + ipilimumab combination therapy in Asian populations has not been demonstrated in clinical practice settings.…”
Section: Introductionmentioning
confidence: 99%